Religious or Spiritual? Empirical Manifestations of Contemporary Changes in Poles’ Self-Declarations and Media Representations - Szymczak, Wioletta; Szulich-Kałuża, Justyna (Verbum Vitae, 2022)
This paper comprises part of the current research on the phenomenon of new spirituality, conducted within the sociology of religion and social communication and media sciences. It aims to analyze selected manifestations of the new spirituality entering into the religious sphere of a religiously homogeneous society based on the example of Poland. A complementary application of quantitative and qualitative methods was proposed. The subject of the analysis is the results of a representative survey in which Poles define themselves in terms of religiosity and spirituality, with examples of their search for content on a new spirituality through online resources using the assumptions of the theory of social representations. The above concept resulted in the bipartite structure of the main part of the article. It was preceded by a theoretical introduction synthetically presenting phenomena identified as key features of new spirituality and ended with a discussion of the results and conclusions. The analyses indicate that, in Polish society, the category of phenomena and processes classified as new spirituality is distinguishable but complex and diverse. In the subsequent stages of the analysis, their socio-demographic determinants were shown, and then the media representations of the new spirituality were identified, categorized, and put into typologies.